Around family biography and its studies. Introductory reflections - Hrehorowicz, Uta; Demkowicz, Leszek (Biografie rodzinne i uczenie się: Tom 8, 2021)
The text presents deliberations concerning a family biography in relation to biographical research approach. A family biography has been presented from the perspective of understanding a family systemically, as a kind of a mechanism favouring its homeostasis. A family biography has been shown as a value for an individual, a group, society and culture. Two approaches have been included in biographical perspective: an individual and a family biography one. Also, the difficulties related to studying family biographies have been pointed to. The presence of the learning process in the context of a family biography has been emphasised, particularly as the process of learning from Others.